2013
DOI: 10.5897/ajmr2013.5354
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and antibacterial activity of Securidaca longepedunculata on selected pathogens

Abstract: Securidaca longepedunculata family Polygalaceae is a tropically distributed medicinal plant. Antibacterial activity of chloroform, methanol and aqueous extracts of the roots and leaves of the plant against some selected microorganisms were shown using standard Kirby-Bauer disk diffusion method. The plants extracts showed inhibitory activity against the tested organisms. The diameter of zones of inhibition exhibited by all the extracts was between 15 and 20 mm. The methanol and the chloroform extracts of the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…Karou et al, (2012) showed that the hydroethanolic root extract of this plant exhibited MIC about 900µg/ml on Klebsiella pneumoniae CIP 52144 ESBL negative. According to Ndamitso et al (2013), E. coli strains were susceptible to roots aqueous extracts. The plant leaves extracts were more active against several Gram negative strains.…”
Section: Discussionmentioning
confidence: 99%
“…Karou et al, (2012) showed that the hydroethanolic root extract of this plant exhibited MIC about 900µg/ml on Klebsiella pneumoniae CIP 52144 ESBL negative. According to Ndamitso et al (2013), E. coli strains were susceptible to roots aqueous extracts. The plant leaves extracts were more active against several Gram negative strains.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that condensed tannins have more antimicrobial properties [25]. Previous studies revealed the presence of tannin only in Securidaca longepedunculata leaves extracts [16,26]. However, tannin is seldom found in Balanites aegyptiaca extract [13,27].…”
Section: Phytochemicalmentioning
confidence: 99%
“…It is commonly used as a medicine in many parts of Africa for the treatment of rheumatic conditions, fever, headache and various other inflammatory conditions [14]. Dried roots powder is also used as a pest control agent in storage, and methanol extracts of the roots have the potential to protect against insect pests and microbial agents [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent disc diffusion study, the aqueous leaf extract yielded zones of inhibition (ZI) of 15 mm against both Escherichia coli and Salmonella typhi, while the chloroform leaf extracts exhibited a ZI of 18 mm against Pseudomonas aeruginosa at a concentration of 7.5 mg/disc (Ndamitso et al, 2013 (Musa et al, 2013). Adebayo and Osman (2012) reported a ZI of 15.10 mm by the ethanol extracts of the root bark at a concentration of 100 mg/ml.…”
Section: Antibacterial Activitymentioning
confidence: 99%